The Länder and German federalism - Gunlicks, Arthur B., 1936- (Issues in German politics., 2003)
This book provides a detailed introduction to how the Länder (the sixteen states of Germany) function not only within the country itself but also within the wider context of European political affairs. Some knowledge of the role of the Länder is essential.